Mobile Application development for labor intermediation as a solution for sectors excluded from the labor market : An Instrument for the definition of public policies - Cambarieri, Mauro (2018)
A social app where local workers can build a reputation based on theirs clients califications. With a strong focus in real life interactions this platform offer a great solution to those who demand a service or product and have interest in compare local options,and also for those who offer a service and want to expand their work opportunities. Registers users can geolocate their working area and detailed their abbilities for free. This project was developed by a workteam established between the National University of Rosario (UNR) and the National University of Río Negro (UNRN). This paper presents technical details of the application and explains the context for its use, as well as associated benefits and necessary technical resources.